Intrasensory Redundancy Facilitates Infant Detection of Tempo: Extending Predictions of the Intersensory Redundancy Hypothesis. (21st March 2015) - Bahrick, Lorraine E.; Lickliter, Robert; Castellanos, Irina; Todd, James Torrence
<x xml:space="preserve">Abstract</x> Research has demonstrated that intersensory redundancy (stimulation synchronized across multiple senses) is highly salient and facilitates processing of amodal properties in multimodal events, bootstrapping early perceptual development. The present study is the first to extend this central principle of the intersensory redundancy hypothesis (IRH) to certain types of intrasensory redundancy (stimulation synchronized within a single sense). Infants were habituated to videos of a toy hammer tapping silently (unimodal control), depicting intersensory redundancy (synchronized with a soundtrack) or intrasensory redundancy (synchronized with another visual event; light flashing or bat tapping). In Experiment 1, 2‐month‐olds showed both intersensory and intrasensory facilitation (with respect to the unimodal control) for detecting a change in tempo. However, intrasensory facilitation was found when the hammer was synchronized with the light flashing (different motion) but not with the bat tapping (same motion). Experiment 2 tested 3‐month‐olds using a somewhat easier tempo contrast. Results supported a similarity hypothesis: intrasensory redundancy between two dissimilar events was more effective than that between two similar events for promoting processing of amodal properties. These findings extend the IRH and indicate that in addition to intersensory redundancy, intrasensory redundancy between two synchronized dissimilar visual events is also effective in promoting perceptual processing of amodal event properties.